Aplikasi Mono-Diasilgliserol dari Fully Hydrogenated Palm Kernel Oil sebagai Emulsifier untuk Margarin - Ria Noviar Triana; Nuri Andarwulan; Arief R Affandi; Wincy Wincy; Eddy KemenadyKemenady (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Margarine is a water-in-oil emulsion product which contains a minimum of 80% fat and a maximum of 18% water. Commonly used emulsifier in margarine is mono-diacylglycerol (MDAG), which can be produced from fully hydrogenated palm kernel oil (FHPKO). Our previous research succeeded in producing MDAG from FHPKO by using glycerolysis method at lab-scale. The objective of this study was to evaluate the application of MDAG from FHPKO as a margarine emulsifier at pilot plant scale. The evaluation includes physicochemical characteristics of the resulting margarine, and physico-sensory characteristics of pound cake and sweet bread produced using the margarine as ingredient. Two concentrations of MDAG from FHPKO in the formulation of margarine were applied; i.e the standard commercial concentration (0.3%) and a concentration 2 times higher (0.74%) than that of standard. The result showed that the physicochemical characteristic of margarine using MDAG from FHPKO as emulsifier had the same specification as that of standard margarine. The performance in application and sensory evaluation of texture, aroma and flavor of pound cake and sweet bread made from margarine with FHPKO MDAG show similarity with product made with commercial emulsifier. The MDAG from FHPKO could be used as an alternative emulsifier for margarine.